Study on the management efficiency of lanthanum/iron co-modified attapulgite on sediment phosphorus load. (February 2023) - Qu, Yihe; Zhao, Li; Jin, Zhenghai; Yang, Haoran; Tu, Chengqi; Che, Feifei; Russel, Mohammad; Song, Xinshan; Huang, Wei
Abstract: Attapulgite co-modified by lanthanum-iron (MT-LHMT) was used to study its effectiveness and mechanism in controlling phosphorus release from sediments. MT-LHMT has high adsorption capacity for phosphate and the maximum adsorption capacity of MT-LHMT to phosphate can reach 75.79 mg/g. The mechanism mainly involved electrostatic action, surface precipitation and ligand exchange between MT-LHMT bonded hydroxyl and phosphate to form La– O –P and Fe– O –P inner-sphere complexes. MT-LHMT has excellent adsorption performance in the pH range of 3–8. In addition to HCO3 −, CO3 2− and HA − had a negative effect on the phosphorus removal of MT-LHMT, while NO3 −, Cl −, SO4 2−, K +, Ca 2+ and Mg 2+ had a positive or no effect on phosphorus removal. MT-LHMT significantly reduced the risk of phosphorus release from overlying water in different dose effects and covering methods, as well as the unstable inactivation of flowing phosphorus, sediment dissolved reactive phosphorus (DRP) and available phosphorus with medium diffusion gradient in thin film in the sediment-water interface (Labile-PDGT ). The MT-LHMT capping wrapped with fabric can reduce the risk of nitrogen release from sediment to overlying water more than only MT-LHMT capping. The results of this study showed that the MT-LHMT capping wrapped with fabric has high potential and can be used as an active capping material to manage the nitrogen and phosphorus load in surface water. Graphical abstract: Image 1 Highlights: MT-LHMT has excellent removal efficiency for phosphate in water. MT-LHMT is used as a geoengineering management tool to control phosphorus release from sediments. MT-LHMT wrapped in fabric can reduce the risk of nitrogen and phosphorus release from sediment to overlying water. The absorption of pore water Labile-PDGT by MT-LHMT in different ways is the key to control phosphorus release.